Depletion of Endothelial or Smooth Muscle Cell-Specific Angiotensin II Type 1a Receptors Does Not Influence Aortic Aneurysms or Atherosclerosis in LDL Receptor Deficient Mice - Rateri, Debra L. (Public Library of Science, 2012)
BACKGROUND: Whole body genetic deletion of AT1a receptors in mice uniformly reduces hypercholesterolemia and angiotensin II-(AngII) induced atherosclerosis and abdominal aortic aneurysms (AAAs). However, the role of AT1a receptor stimulation of principal cell types resident in the arterial wall remains undefined. Therefore, the aim of this study was to determine whether deletion of AT1a receptors in either endothelial cells or smooth muscle cells influences the development of atherosclerosis and AAAs. METHODOLOGY/PRINCIPAL FINDINGS: AT1a receptor floxed mice were developed in an LDL receptor −/− background. To generate endothelial or smooth muscle cell specific deficiency, AT1a receptor floxed mice were bred with mice expressing Cre under the control of either Tie2 or SM22, respectively. Groups of males and females were fed a saturated fat-enriched diet for 3 months to determine effects on atherosclerosis. Deletion of AT1a receptors in either endothelial or smooth muscle cells had no discernible effect on the size of atherosclerotic lesions. We also determined the effect of cell-specific AT1a receptor deficiency on atherosclerosis and AAAs using male mice fed a saturated fat-enriched diet and infused with AngII (1,000 ng/kg/min). Again, deletion of AT1a receptors in either endothelial or smooth muscle cells had no discernible effects on either AngII-induced atherosclerotic lesions or AAAs. CONCLUSIONS: Although previous studies have demonstrated whole body AT1a receptor deficiency diminishes atherosclerosis and AAAs, depletion of AT1a receptors in either endothelial or smooth muscle cells did not affect either of these vascular pathologies.